2020
DOI: 10.1021/acs.analchem.0c02479
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Susceptibility-Based Protein Detection Using Magnetic Levitation

Abstract: Magnetic levitation, which is a magnetic phenomenon of levitating particles suspended in a paramagnetic liquid under a nonuniform magnetic field, is a powerful tool for determining densities and magnetic properties of micro- and nanoparticles. The levitation height of particles in the magnetic field depends on the magnetic susceptibility and density difference between the object and the surrounding liquid. Here, we developed a magnetic susceptibility-based protein detection scheme in a low-cost and miniaturize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Several studies reported the biochemical sample handling using microfluidic and magnetic beads to capture protein markers [9,10]. In addition, one of the notable reports proposed a magnetic susceptibility-based protein detection using magnetic levitation [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported the biochemical sample handling using microfluidic and magnetic beads to capture protein markers [9,10]. In addition, one of the notable reports proposed a magnetic susceptibility-based protein detection using magnetic levitation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another popular method to avoid the requirement of an electric pump in the microfluidic system is the capillary-driven chip [11,[14][15][16]. The capillary attraction can be driven by porous or cellulose materials, such as thread, woven fabrics, paper [17][18][19][20][21][22], and cellulose sponges [16,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…[48] For protein detection, a magnetic susceptibility-based MagLev platform was integrated with an inverted microscope for imaging. [37] The principle of magnetic susceptibility is based on labeling the protein with magnetic nanoparticles (MNPs), thus changing the beads' magnetic susceptibility. Generally, polymer microspheres levitate in the midpoint between the two magnets because they have no magnetic susceptibility.…”
Section: Protein Analysismentioning
confidence: 99%
“…The magnetic susceptibility difference between the object and the medium, under a magnetic field, is exploited to suspend particles, [ 37 ] which is either based on positive or negative magnetophoresis. In positive magnetophoresis, paramagnetic materials are manipulated in a diamagnetic medium.…”
Section: Magnetic Levitation Fundamentalsmentioning
confidence: 99%
See 1 more Smart Citation